The Values of Independent Hip-Hop in the Post-Golden Era Hip-Hop's Rebels - Vito, Christopher (Springer Nature, 2019)
Utilizing a mixed-methods approach, this book uncovers the historical trajectory of U.S. independent hip-hop in the post-golden era, seeking to understand its complex relationship to mainstream hip-hop culture and U.S. culture more generally. Christopher Vito analyzes the lyrics of indie hip-hop albums from 2000-2013 to uncover the dominant ideologies of independent artists regarding race, class, gender, sexual orientation, and social change. These analyses inform interviews with members of the indie hip-hop community to explore the meanings that they associate with the culture today, how technological and media changes impact the boundaries between independent and major, and whether and how this shapes their engagement with oppositional consciousness. Ultimately, this book aims to understand the complex and contradictory cultural politics of independent hip-hop in the contemporary age.